PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN NON MEDIS PADA RSUD. ASEMBAGUS SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Akbar, Ilham; Tulhusnah, Lusiana; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2023)
The research objective is to determine the effect of work motivation and work discipline on the performance of non-medical employees at RSUD. Asembagus Situbondo with Job Satisfaction as an Intervening Variable. The sampling technique used in this study is a saturated sample with a total sample of 50 employees. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that work motivation has a positive and significant effect on job satisfaction, work discipline has a positive and significant effect on job satisfaction, work motivation has a positive and significant effect on employee performance, work discipline has a negative but significant effect on Employee performance, job satisfaction has a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance through job satisfaction, work discipline has a positive and significant effect on employee performance through job satisfaction.